Influence of salt stress on the mineral composition of Arthrospira platensis grown in an extreme environment in southern Algeria - LAICHE, Ammar Touhami; BESSEI, Abdelmalek (University of Eloued جامعة الوادي, 2018)
The salinity of Saharan waters poses a problem for the growth of aquatic species. The cultivation of spirulina requires a culture medium with a salinity of about 13 g / l. The study consisted in the cultivation of spirulina in environments that differ in their salt content; D0: a control, D1: 13g / l, D2: 26g / l and D3: 39g / l. Daily reports of pH and electrical conductivity have been made. After obtaining the biomass, the determination of the level of certain spirulina mineral elements (Ca ++, Na + , K + , Mg ++, Fe ++) was carried out. According to the results, salinity does not seem to be a limiting factor for the growth of this species. Moreover, it seems that the salinity factor has little influence on the mineral composition of Spirulina, with a variability of pH values and electrical conductivity. Therefore, the cultivation of this species of seaweed in Saharan waters affected by a high salt content, seems possible and possible
Articale in International Journal of biological and Agricultural Research Vol. 01 N. 02
Keywords: Arthrospira platensis, Salinity, Biomass, Minerals.